High MMP-9 and TNF-α expression increase in preterm premature rupture of membranes - Sulistyowati, Sri; Zakia, Yuniarsih; Khasan, Soetrisno (Faculty of Medicine, Trisakti University, 2016)
Preterm delivery is one of the causes of high perinatal morbidity and mortality. Matrix metalloproteinase 9 (MMP-9) is important for extracellular matrix (ECM) remodeling and may cause preterm labor and premature rupture of membranes (PROM). Tumor necrosis factor-α (TNF-α) as a pro-inflammatory cytokine plays a role in stimulating uterine activity and cervical ripening by degrading the ECM of the amniotic membranes through MMP-9. This study aimed to determine differences between MMP-9 and TNF-α expression of the membranes in preterm delivery with premature rupture of membranes (PPROM) and without PROM.MethodsAn analytic observational study with cross-sectional approach was conducted in 24 subjects, who were divided into 2 groups, with 12 subjects in the preterm delivery group with PROM and 12 subjects in the preterm delivery group without PROM. The expression of MMP-9 and TNF-α in the amniotic membrane was determined by immunohistochemistry. Data were analyzed using the t test.ResultsMMP-9 expression in the amniotic membrane of preterm delivery subjects with PROM (8.6 ± 3.1%/field) differed significantly with that of preterm delivery subjects without PROM (5.5 ± 2.3 %/ field) (p=0.001). TNF-α expression in the amniotic membrane of preterm delivery subjects with PROM (8.0 ±3.0%/field) also differed significantly with that of preterm delivery subjects without PROM (3,3 ± 1.5%/field) (p=0.000).ConclusionExpression of MMP-9 and TNF-α was higher in the amniotic membrane of preterm delivery subjects with PROM than in preterm delivery subjects without PROM and can thus be used as predictor to avoid PPROM.